Cigarette smoke inhibits ROCK2 activation in T cells and modulates IL-22 production. (March 2016) - Weng, Chien-Huan; Gupta, Sanjay; Geraghty, Patrick; Foronjy, Robert; Pernis, Alessandra B.
Highlights: Direct exposure of CD 4+ T cells to cigarette smoke extract (CSE) enhances IL-22 production. Treatment with CSE inhibits the RhoA-ROCK2 signaling pathway and reduces phosphorylation of IRF4. Decreased activation of the RhoA-ROCK2 pathway by CSE is associated with a reduction in the activation of ARHGEF1, an upstream regulator of the RhoA-ROCK axis. Abstract: Gene-environment interactions are known to play a key role in the development of rheumatoid arthritis (RA). Exposure to cigarette smoke (CS) is one of the strongest environmental risk factors associated with RA and has been shown to mediate a range of complex immunomodulatory effects from decreased T and B cell activation to depressed phagocytic function. The effects of CS on the function of TH 17 cells, one of the key TH effector subsets implicated in RA pathogenesis, are not fully understood. IRF4 is one of the crucial transcription factors involved in TH -17 differentiation and is absolutely required for the production of IL-17 and IL-21 but, interestingly, inhibits the synthesis of IL-22. The production of IL-17 and IL-21 by IRF4 can be augmented by its phosphorylation by the serine-threonine kinase ROCK2. Given that CS has been reported to increase ROCK activity in endothelial cells, here we investigated the effects of CS on the ROCK2-IRF4 axis in T cells. Surprisingly, we found that CS leads to decreased ROCK2 activation and IRF4 phosphorylation in T cells. This effect was associated with increased IL-22 production. Using a GEF pull-down assay we furthermore identify ARHGEF1 as a key upstream regulator of ROCK2 whose activity in T cells is inhibited by CS. Thus CS can inhibit the ROCK2-IRF4 axis and modulate T cell production of IL-22.